Visibility of PM Najib’s 100 days in office: a framing approach of his political branding identity - Yuslinda Mat Yassin; Hasmah Zanuddin (Universiti Kebangsaan Malaysian, 2012)
Political branding is gaining its popularity as it is competitive in terms of voters’ market. With the involvement of consumer or voters’ choices, the branding principles have been practically functional. This paper examined four main newspapers identifying the visibility of political branding attributes of Malaysian 6th Prime Minister (PM), Dato’ Seri Najib Tun Abdul Razak during his 100 days in office. This study investigated framing and branding attributes of PM’s political strategies, visibility and images in the media. Five framing attributes adopted and modified from Semetko & Valkenburg, (2000) namely responsibility, economic consequences, morality, conflict and human interest were used. While branding attributes consists of reassurance, value-based, credible, aspirational and simple/unique. Cramer’s V, Phi value and analysis of variance (anova) statistical analysis were used to confirm the hypotheses.